Concurrent and longitudinal associations between touchscreen use and executive functions at preschool-age - Mortimer, Alicia; Fiske, Abigail; Biggs, Bethany; Bedford, Rachael; Hendry, Alexandra; Holmboe, Karla (Frontiers in Developmental Psychology, 2024)
The prevalence of touchscreen devices has recently risen amongst young children. Some evidence suggests that increased touchscreen use may be negatively related to preschool-age children’s executive functions (EFs). However, it has been argued that actively interacting with touchscreen devices (e.g., via creative apps for drawing) could better support EF development compared to passive use (e.g., watching videos; Christakis, 2014). There is a pressing need to understand whether the type of use can explain potential associations between touchscreen use and EF. By following up longitudinally on an infant sample, now aged 42-months (N = 101), the current study investigates the relative contributions of passive and active touchscreen use, measured concurrently at 42-months and longitudinally from 10-to-42-months, on parent-reported EFs. A multivariate multiple regression found no significant negative associations between touchscreen use and preschool EF. There was a significant positive association between active touchscreen use at 42-months and the BRIEF-P Flexibility Index. These results are consistent with an earlier study’s findings in the same sample at infancy, suggesting that the moderate levels of early touchscreen use in this sample are not significantly associated with poorer EF, at least up to preschool-age.